Pdgfra and Pdgfrb Genetically Interact in the Murine Neural Crest Cell Lineage to Regulate Migration and Proliferation - Mo, Julia; Long, Robert; Fantauzzo, Katherine A. (Frontiers in Physiology, 2020)
Cranial neural crest cells (cNCCs) are migratory, multipotent cells that originate from the forebrain to the hindbrain and eventually give rise to the cartilage and bone of the frontonasal skeleton, among other derivatives. Signaling through the two members of the platelet-derived growth factor receptor (PDGFR) family of receptor tyrosine kinases, alpha and beta, plays critical roles in the cNCC lineage to regulate craniofacial development during murine embryogenesis. Further, the PDGFRs have been shown to genetically interact during murine craniofacial development at mid-to-late gestation. Here, we examined the effect of ablating both Pdgfra and Pdgfrb in the murine NCC lineage on earlier craniofacial development and determined the cellular mechanisms by which the observed phenotypes arose. Our results confirm a genetic interaction between the two receptors in this lineage, as phenotypes observed in an allelic series of mutant embryos often worsened with the addition of conditional alleles. The defects observed here appear to stem from aberrant cNCC migration, as well as decreased proliferation of the facial mesenchyme upon combined decreases in PDGFR and PDGFR signaling. Importantly, we found that PDGFR plays a predominant role in cNCC migration whereas PDGFR primarily contributes to proliferation of the facial mesenchyme past mid-gestation. Our findings provide insight into the distinct mechanisms by which PDGFR and PDGFR signaling regulate cNCC activity and subsequent craniofacial development in the mouse embryo.